Faktor-Faktor Dimensi Budaya dalam Kepatuhan Minum Obat Kusta - Soamole, Idham; Sukartini, Tintin; Padoli, Padoli (FORIKES, 2022)
The success of leprosy treatment can be influenced by cultural dimensions. This study aims to determine the relationship between the cultural dimension and the adherence factor for treatment of leprosy patients. This study is a systematic review using databases including: ProQuest, Sciencedirect, EBSCO and SCOPUS. The keywords used were “factors or causes”, “culture or cultural or ethnicity”, “leprosy or Hansen's disease”, “treatment or intervention or therapy”, dan “adherence or compliance”. The selection process referred to the PRISMA guidelines, so that 15 articles were obtained that met the inclusion criteria. The results of the review show that the number of leprosy patients who do not participate in the leprosy treatment program is influenced by the cultural dimension. Sufferers also believe that leprosy can heal itself and can be treated with a spiritual approach. Thus, it is concluded that culture still greatly influences the compliance process in implementing the leprosy treatment program.Keywords: leprosy; culture; medication adherence ABSTRAK Keberhasilan pengobatan kusta dapat dipengaruhi oleh dimensi budaya. Studi ini bertujuan untuk mengetahui hubungan antara dimensi budaya dengan faktor kepatuhan berobat penderita kusta. Studi ini merupakan systematic review menggunakan database antara lain: ProQuest, Sciencedirect, EBSCO dan SCOPUS. Kata kunci yang digunakan adalah “factors or causes”, “culture or cultural or ethnicity”, “leprosy or Hansen's disease”, “treatment or intervention or therapy”, dan “adherence or compliance”. Proses seleksi mengacu kepada pedoman PRISMA, sehingga didapatkan 15 artikel yang memenuhi kriteria inklusi. Hasil review menunjukkan bahwa banyaknya penderita kusta yang tidak mengikuti program pengobatan kusta dipengaruhi oleh dimensi budaya. Penderita juga percaya bahwa kusta dapat sembuh sendiri dan dapat diobati dengan pendekatan spiritual. Dengan demikian disimpulkan bahwa budaya masih sangat mempengaruhi proses kepatuhan dalam melaksanakan program pengobatan kusta.Kata kunci: kusta; budaya; kepatuhan minum obat